Container logistics and maritime transport / Routledge Studies in Transport Analysis - Song, Dong-Ping (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This book provides a coherent and systematic view of the key concepts, principles and techniques in maritime container transport and logistics chains including all the main segments: international maritime trade and logistics, freight logistics, container logistics, vessel logistics, port and terminal management, and sustainability issues in maritime transport. Container Logistics and Maritime Transport emphasizes analytical methods and current optimization models to tackle challenging issues in maritime transport and logistics. This book takes a holistic approach to cover all the main segments of the container shipping supply chains to achieve an efficient and effective logistics service system across the entire global transport chain. Sustainability issues such as social concern and emissions from shipping and ports are also discussed. Cutting-edge optimization models are presented and explained to tackle various strategic, tactical and operational planning problems. The book will help readers better understand operations management in global maritime container transport chain. It will also provide practical principles and effective techniques and tools for researchers to push forward the frontiers of knowledge and for practitioners to implement decision support systems. It will be directly relevant to academic courses related to maritime transport, maritime logistics, transport management, international shipping, port management, container shipping, container logistics, shipping supply chain and international logistics"--
Includes bibliographical references and index.
Keywords: Shipping; Containerization; Business logistics